Registration Information System for Participants in the Basic Religious Ability Test at the Islamic University of Kuantan Singingi - Febri Haswan; Sri Chairani (Sean Institute, 2022)
Information technology is marked by the birth of the computer and its very fast development where information technology is now very much needed by various parties, both companies, state civil servants, private companies, universities and so on. At present the use of information technology at the Institute for Community Service Research and Islamic Da'wah at the Islamic University of Kuantan Singingi (LPPMDI UNIKS) has not been fully used. Islamiyah has not been carried out optimally where previous data processing was felt to be ineffective, therefore there is a need for a new innovation to make it easier for the Da'wah Islamiyah section to manage data, one of the data that must be managed is the Basic Religious Ability Test for students at the Islamic University of Kuantan Singingi environment where this data is very necessary for students and LPPMDI UNIKS as a report to the Dean, Study Program and Deputy Chancellor for Field 1 at the Islamic University of Kuantan Singingi, besides that it is also used as one of the conditions that must be met by students who will graduate.